THE RELATIONSHIP OF ANXIETY WITH HYPERTENSION FOR ELDERLY IN LAMPE WORKING AREA OF EAST RASANAE PUBLIC HEALTH CENTER BIMA - Wijaya, Alwan; Dwiatmojo, Nia Firdianty; Julianto, Heri; Putra, Ageng Abdi; Astuti, Febriati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The increasing number of elderly people pays special attention to those who are experiencing an aging process. There are some problems that need special attention as the results of aging, such as physical, cognitive, emotional, social, and sexual changes. The purpose of this study is to find out the relationships between anxiety with hypertension of the elderly in subdistrict of Lampe working area of East Rasanae Public Health Center, Bima City.The research design of this study is cross sectional with correlation study approach. Around 23 elderly with hypertension was used as sample in the study. Sampling techniques used was total Sampling. The instrument used was questionnaires and spermank rank ws used for data analysis used.Based on the results of the questionnaire, 12 respondents showed no symptoms at all (52.2%), mild anxiety was amounted to 10 respondents (43.5%). 16 respondents (69.6%) were considered to have Hypertension at Stage I. This could also be seen from the test value analysis between anxiety and hypertension of the elderly where p value was greater than the significant level of 0.05 (p value>α) so that Ha was rejected and H0 was accepted, meaning that there was no relationship between anxiety and hypertension of the elderly in the subdistrict of Lampe working area of East Rasanae Public Health Center, Bima City.From the analysis, it can be concluded that there was no relationship between anxiety and hypertension of the elderly. Anxiety in the elderly is not a major factor that can trigger hypertension, yet there are other factors that should be considered by the elderly such as lifestyle and hereditary factors.